Dinamika Penentuan Awal Bulan Kamariah Nahdatul Ulama: sebelum dan sesudah adanya formulasi kriteria imkan rukyat - Afifah Mulya Alamsyah; Muhammad Ihtirozun Ni’am (Astroislamica: Journal of Islamic Astronomy, 2025)
Nahdatul Ulama is a large Islamic organisation in Indonesia that has many people and is engaged in religious sosial affairs. In NU, there is a special Lajnah that deals with phalactic issues, namely Lajnah Falakiyyah Nahdatul Ulama. However, the determination made by NU initially only used Rukyat which of course invited discourse on determining the beginning of the month using rukyat and imkanrukyat. This research has a formulation of how Nahdatul Ulama before and after the existence of imkanrukyat and aims to find out how NU addresses the determination of the beginning of the Kamariah month, especially before and after the existence of Imkan ar Rukyat in Indonesia and how the paradigma of determining the beginning of the Kamariah month which was originally only three months in a hijri year, then changed to every month in a hijri year. This type of research is library research. And it is concluded that Nahdatul Ulama as an Islamic organisation is an organisation that is very open to change as long as it does not violate the Islamic Aqidah, and in LFNU itself there is a dynamic paradigma. Of course the changes in the determination of the beginning of the month changed, when before the imkanrukyat LFNU was only based on rukyat alone, and rukyat was carried out only in three major months, then after the Imkan appeared, rukyat was carried out in six major months, and then became every beginning of the Hijri month.